Higher education and social cohesion : experience in Sabah and Sarawak - Pang, Vincent; Ahi, Anak Sarok; Lai, Yew Meng.; Mariappan, Kntayya.; Morshidi, Sirat; Nona M., Nistah (UNIMAS Publisher, 2013)
This publication documents a research entitled : Higher Education and Social Cohesion in Sabah and Sarawak" which was funded by the Ministry of Higher Education through the National Higher Education Research Institute. The authors and researchers record their sincere appreciation to the Ministry and Institute for the sponsorship. Social cohesion is a highly valued and essential societal condition for countries with the diverse ethnic, cultural and religious demography. It is a key concern in view of its significance in fostering political stability and sustaining economic development under such a pluralistic and potentially volatile social milieu.